Legal Framework of Air Rifle Modification in Patent and Industrial Design Law: Kerangka Hukum Modifikasi Senapan Angin dalam Hukum Paten dan Desain Industri - Utomo, Agung Ridzal; Phahlevy, Rifqi Ridlo (Indonesian Journal of Law and Economics Review, 2025)
General Background: The modification of air rifles has become increasingly common in Indonesia, raising complex questions regarding legal boundaries and intellectual property protection. Specific Background: These modifications often involve both technical and aesthetic changes that may intersect with patent and industrial design rights. Knowledge Gap: Previous research has not thoroughly addressed how such modifications align with Law No. 13 of 2016 on Patents and Law No. 31 of 2000 on Industrial Designs, particularly when carried out for commercial purposes. Aims: This study aims to analyze the legal implications of air rifle modifications from the perspective of patent and design law. Results: The findings indicate that personal modifications pose minimal legal risk, while commercial alterations without permission from patent or design holders can lead to civil and criminal sanctions. Novelty: This paper provides a structured legal interpretation differentiating technical and aesthetic alterations under respective laws. Implications: The study contributes to clearer regulatory understanding and encourages compliance with intellectual property rights in mechanical innovation and design practices. Highlights: • Legal analysis of air rifle modification under Indonesian patent and design law • Differentiation between technical and aesthetic modifications • Legal consequences of unauthorized commercial modifications Keyword: Air Rifle, Patent Law, Industrial Design, Modification, Intellectual Property